Android App to Measure Linguistic Intelligence of Elementary Students - Muttaqin, Alif Noorachmad; Lubis, Muharman; Sandy, Muhammad Dwi Hary (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
There is an opinion that the critical period of language development occurs between the ages of two years until puberty. During this period, especially around the age of six, children tend to avoid using passive vocabulary or complex sentence forms such as conditional commands. However, as they grow older, up to and even beyond the age of nine, their comprehension of grammatical structures and ability to process more complex linguistic forms gradually improves. Given the importance of this developmental window, formal educational institutions play a crucial role in fostering various types of student intelligence, including linguistic intelligence. Linguistic intelligence refers to the capacity to effectively use language to express thoughts, whether through speaking, reading, listening, or writing. This type of intelligence not only supports academic achievement but also enhances communication skills essential in daily life. In response to the need for effective tools in education, this study introduces the development of the LIAA (Linguistic Intelligence Assessment Android) application. This mobile-based application is designed to assist teachers in efficiently assessing and identifying the linguistic intelligence levels of elementary school students through a user-friendly and systematic digital platform.